A consistent, scalable model for Eulerian spray modeling. (July 2016) - Pandal, A.; Pastor, J.M.; García-Oliver, J.M.; Baldwin, E.; Schmidt, D.P.
Highlights: A new Σ -Y Eulerian model construction has been built around an IMEX-RK3 algorithm. A density-based algorithm is used to resolve inconsistencies of segregated solutions. The new model and the existing one have been compared on diesel sprays simulations. New model improves the accuracy, stability and parallel efficiency of simulations. New Runge-Kutta construction has long-term value for its potential. Abstract: Despite great practical interest in how sprays emanate from fuel injectors, the near-nozzle region has remained a challenge for spray modelers. Recently, Eulerian models have shown promise in capturing the fast gas-liquid interactions in the near field. However, with the inclusion of compressibility, it can be difficult to maintain consistency between the hydrodynamic and thermodynamic variables. In order to resolve numerical inconsistencies that occur in segregated solutions of Eulerian spray model equations as well as to provide good scalability and stability, a new construction of a Σ -Y model is introduced. This construction is built around an IMEX-RK3 algorithm which offers accuracy and efficiency. The new algorithm is compared to an existing implementation for speed and is validated against experimental measurements of spray evolution in order to test the accuracy. The predictions of the new construction are slightly more accurate and, when tested on 256 processors, are 34 times faster.